Adverse drug reactions in elderly: a five-year review of spontaneous reports to the Portuguese pharmacovigilance system. Issue 1 (2nd January 2021) - Monteiro, Cristina; Duarte, Ana Paula; Alves, Gilberto
ABSTRACT: Background : Adverse drug reactions (ADRs) are responsible for considerable morbidity and mortality in elderly. This study aimed to characterize the ADRs profile in Portuguese elderly patients, thus enhancing ADRs knowledge in this vulnerable population. Methods : All spontaneous ADRs reported to the Portuguese Pharmacovigilance System from 2013 to 2017 were examined. However, considering the aim of this study, ADRs referring to patients aged 65 and over were analyzed in higher detail and compared with those reported in non-elderly adults. Results : Considering the age of 65 years and above, 3692 spontaneous reports of suspected ADRs were analyzed. The suspected ADRs most frequently reported fall within the categories of general disorders and administration site conditions, and skin and subcutaneous tissue complaints. Regarding therapeutic agents, the antineoplastic drugs were the most common involved. Among the 2458 cases of serious ADRs reported, 34.0% led to hospitalization and in 5.8% of them occurred a fatal outcome. The antineoplastic and antithrombotic drugs were the most represented pharmacotherapeutic groups of suspected drugs involved in patient's death (25.0% and 13.6%, respectively). Conclusions : Most of the suspected ADRs were classified as serious. The majority of them were expected, so preventable, highlighting the importance of improving medication use in elderly.